Respon Warganet Mengenai Pernikahan Beda Agama - Riesardhy, Anastasia Winanti (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Indonesia's diversity creates opportunities for interfaith marriages. Although these marriages cannot be legally registered in Indonesia, their prevalence is increasing. This controversy stems from the belief that marriage is a private matter and shouldn't be regulated by the state. This study aims to describe public sentiment towards interfaith marriage through the Cretivox YouTube video "Suami Kristen, Istri Islam." In communication, interaction in social media, in this case commenting on YouTube videos, falls into the category of computer mediated communication (CMC). CMC theory is a type of integrable communication in which two or more people can only communicate or exchange information through a computer or referring to any kind of communication in which computer technology is used as a medium to connect individuals or groups of people to talk to each other. In research using CMC theory, Netnography is the most suitable approach where netnography is defined as a qualitative research methodology that adapts ethnographic research techniques to study the culture and community that occurs in CMC. This research found that public sentiment is generally positive, though some responses disagree. Some public argue against interfaith marriages, citing contradictions with Islamic values, while others oppose them as a precaution. Some comments shared their own interfaith marriage experiences, and some expressed hesitation or plans to enter such marriages.